Dried Blood Spot Reference Intervals for Steroids and Amino Acids in a Neonatal Cohort of the National Children's Study. (6th January 2020) - Dietzen, Dennis J; Bennett, Michael J; Lo, Stanley F; Grey, Vijay L; Jones, Patti M
Abstract: BACKGROUND: Reference intervals from children are limited by access to healthy children and their limited blood volumes. In this study we set out to fill gaps in pediatric reference intervals for amino acids and steroid hormones using dried blood spots (DBS) from a cohort of the National Children's Study. METHODS: Deidentified DBS annotated with age, birthweight, sex, and geographic location were obtained from 310 newborns aged 0–4 days and analyzed for 25 amino acids and 4 steroid hormones using LC-MS/MS. Nonparametric statistical approaches were used to generate the 2.5th–97.5th percentile distributions for newborns. Paired plasma/DBS specimens were used to mathematically transform DBS reference intervals to corresponding plasma intervals. RESULTS: 10 of 25 DBS amino acid distributions were dependent on sex. There was little correlation with age, birthweight, or geographic location over the first 4 days of life. In most cases, transformation of DBS distributions to plasma distributions faithfully reflected independent studies of newborn plasma amino acid distributions. In general newborn steroid distributions were negatively correlated with age and birthweight over the first 4 days of life. Data distributions for the 4 steroids were not found related to geographic location, but testosterone concentrations displayed sex dependence. Transformation of DBS distributions to plasma intervals did not faithfully replicate other neonate steroid reference intervals determined directly with plasma. CONCLUSIONS: These data demonstrate the feasibility and utility of deriving newborn reference intervals from large numbers of archived DBS samples such as those obtained from the National Children's Study biobank.